2022
DOI: 10.1186/s12991-022-00388-0
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorders (PD) and interpersonal violence (IV) during COVID-19 pandemic: a systematic review

Abstract: Not only did the ongoing CoronaVIrus Disease-19 (COVID-19) pandemic cause a massive number of casualties, but also there is growing concern that the burden of its psychological aftermaths will only show up years down the road. This systematic review summarises the existing literature reporting the impact of COVID-19 on personality disorders (PDs)-related violence. MEDLINE and APA PsycINFO were independently searched for relevant studies by two authors. Eligible studies had to be identifiable through database s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…Based on the characteristics of these disorders, Preti et al 4 hypothesized that the pandemic would be poorly tolerated in people with personality disorders, but a subsequent systematic review found only a few small clinical studies and low-quality surveys. 5 The analysis presented here suggests that people with personality disorders in Alberta manifested increased rates of hospitalization during early phases of the pandemic. Indeed, the increase was more pronounced than the widely reported increase in admissions for eating disorders.…”
mentioning
confidence: 78%
“…Based on the characteristics of these disorders, Preti et al 4 hypothesized that the pandemic would be poorly tolerated in people with personality disorders, but a subsequent systematic review found only a few small clinical studies and low-quality surveys. 5 The analysis presented here suggests that people with personality disorders in Alberta manifested increased rates of hospitalization during early phases of the pandemic. Indeed, the increase was more pronounced than the widely reported increase in admissions for eating disorders.…”
mentioning
confidence: 78%
“…4,5 Most studies on the impact of the pandemic on patients with personality pathology have focused on borderline personality disorder (BPD). 6 Social distancing measures during the pandemic and an increased sense of loneliness are serious aggravating factors for patients with BPD and may cause anxieties of abandonment and rejection, social withdrawal, and feelings of emptiness. Consequently, the patient's susceptibility to risky behaviors and substance use increases.…”
mentioning
confidence: 99%
“…7 Several papers have studied the number of patients with PD or self-harm visits to hospital emergency departments during the pandemic. 6,9 In the studies that examined self-injury, the psychiatric diagnosis was not recorded, but they are mentioned here because the presence of self-harm is closely associated with PD. 10 The number of emergency department visits of patients with PD or self-harm was found to be increased in some papers, decreased in others, and stable in others, compared to the previous year.…”
mentioning
confidence: 99%
See 2 more Smart Citations